PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Kurniya Alda Syafitri; Herawati Khotmi; Elvina Setiawati (Akuntabel: Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of financial ratios (Current Ratio, Return On Equity, Net Profit Margin, Earning Per Share, and Debt to Equity Ratio) on stock prices. This type of research is associative research using a quantitative approach to determine the relationship between two or more variables. The type of data used in this study is secondary data obtained from annual financial reports and closing price lists. The sampling technique uses purposive sampling method. The sample in this study was 23 banking companies multiplied by 5 years, namely 115 samples. This study used a data analysis model in the form of multiple linear regression using SPSS 25 software. The results of this study concluded that partially: a). Current Ratio has a significant negative effect on stock prices, b). Return On Equity has a significant negative effect on stock prices, c). Net Profit Margin has a significant positive effect on stock prices, d). Earning Per Share has a significant positive effect on stock prices, and e). Debt to Equity Ratio has no effect on stock prices in banking companies listed on the Indonesia Stock Exchange (IDX).